Movimentos migratórios no contexto de abertura e fechamento das fronteiras agrícolas - Schneider, Iara Elisa (2008)
The aim of this work is to understand and analyze the migratory flows that were processed internally in our country during the time the opening and closing of the agricultural borders. This work seeks to realize a "study of case" about the flows which promoted the developed of the population of the West regions of "Parana" and "Alto Teles Pires" in the State of Mato Grosso. These regions were denominated poles of attraction and represented opportunities with the opening of the agricultural borders. The analysis of the migration flows is important to observe the way that economic and social integration of migrants happened within the agricultural borders and to identify how these migrants acted in the rural and urban activities, as well as their importance to the regional development. Moreover, this paper discuss two different political moments. One of them is before the establishment of the military regime and the other one is after this regime in 1964. The work also analyzes the political ways of colonization in these periods, in which the West region of Parana can be detached. This region was colonized from 1940, during the government of Getulio Vargas and the region of Alto Teles Pires in Mato Grosso was colonized after 1960, during the military regime. A comparative analysis of the both studies was realized in order to discuss how the occupation happened and the development of these regions, which were colonized in different economic and political ways and in special contexts. In order to understand the main questions that motivated this paper, databases were used from the Instituto Brasileiro de Geografia e Estatística - (IBGE); Instituto Paranaense de Desenvolvimento Econômico e Social - IPARDES; Instituto de Pesquisa Econômica e Aplicada - IPEA and from the Núcleo de Estudos de Popução - NEPO from Unicamp. An intense review of the literature about the migration, agricultural border and regional development was also done.